Reorientasi Kajian Ushul Fiqh - Akh. Minhaji (Al-Jami'ah Research Centre, 1999)
Basically, uṣūl al-fiqh is understood as a methodology to understand Islamic teaching, not only tools to understand Islamic Law as it is perceived by common people. Uṣūl al-fiqh grows and develops throughout Islamic history. It has significant position since its inception. It has been produced many scholars who later formulate formulas that exist even today. Eventhough the science of uṣūl al-fiqh plays an important role in Islamic studies, but not all of Muslim scholars pay full attention to it. Even, there is a critical notion that the science of uṣūl al-fiqh is no longer compatible to solve the problems of Islamic community. Based on this frame of thought, the present author tries to investigate the historical aspect of uṣūl al-fiqh and seek the cause of its stagnancy. The author finds that there are two kinds of approaches recognized in uṣūl al-fiqh: doctrinal normative-deductive and empirical-historical-inductive. These two approaches cannot be separated. However, in the practical level, certain scholars usually apply one approach and disregard another. As a result, their product tend to be more idealistic than touching to the real problem. Finally, the author suggests to combine both methods with respect to other disciplines, particularly social sciences and their methodology.